Web-Based Database and SMS to Facilitate Healthcare Medical Emergency - Hameed, Shihab A.; M. Sharifudeen, Shahina Shabnam; Chek Nuh, Nur Hafizah; Salim, Nur Huda; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran (2011)
Healthcare and medical emergency are essential systems in human life; so that many countries work toward having it. Investigation of Malaysian case shows that it suffer from locality, missing of unified electronic medical record EMR and lack of utilizing Internet, multimedia, wireless and real time technologies. Other drawbacks include: Difficulty in searching and viewing up to date records for patient, doctor, hospital, and drug, since many of such records are still kept in filing cabinet. This leads to difficulty in communication, hard to manage and exchange patient data between various medical units. The fully computerizing and combining of such medical systems will lead to produce a Novel Integrated Healthcare Medical Emergency Model (IHMEM). IHMEM includes three main parts: The web based database, the intelligent agent, and the mobility. This paper focuses on developing an interactive web-based database with unified EMR as well as using SMS facilities, where all hospitals, healthcare and emergency centers can view the patient record simultaneously, exchanging, managing and collaborate on sharing resources between medical units. A prototype for this work is build and sample of implementation results for interactive database and SMS facilities are shown. IHMEM can be easily customized to be suitable for other countries.